2022
DOI: 10.7759/cureus.22077
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Association Between Coronavirus Disease 2019 and Normocomplementemic Rapidly Progressive Glomerulonephritis-Crescentic Immunoglobulin A Nephropathy: A Report of Two Pediatric Cases

Abstract: Coronavirus disease 2019 , caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been predominately associated with respiratory illness. Acute kidney injury (AKI) is the most common reported kidney involvement. Kidney complications, including proteinuria, hematuria, and rarely collapsing glomerulopathy (CG), a form of focal segmental glomerulosclerosis (FSGS), are also well known now and are frequently documented in the literature published so far.We present two cases of glomeruloneph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…After a brief follow-up period, the kidney function of none of the patients returned to its baseline level. 2 N et al 3 presented a case of glomerulonephritis in the setting of AKI in a child with COVID-19. Kidney biopsy specimens showed IgA nephropathy with crescentic glomerulonephritis, acute tubular injury, and focal medium-artery vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…After a brief follow-up period, the kidney function of none of the patients returned to its baseline level. 2 N et al 3 presented a case of glomerulonephritis in the setting of AKI in a child with COVID-19. Kidney biopsy specimens showed IgA nephropathy with crescentic glomerulonephritis, acute tubular injury, and focal medium-artery vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…Another case study reported on 2 patients (13- and 16-year-old boys) who developed severe, rapidly progressive GN and end-stage renal disease after COVID-19 in India. A kidney biopsy confirmed immunoglobulin A (IgA) nephropathy with crescentic GN, acute tubular injury, and focal medium-artery vasculitis [ 34 ].…”
Section: Kidney Complications Associated With Covid-19 Infection In C...mentioning
confidence: 99%
“…133 (G, H) In SARS-COV-2-related Immunoglobulin A (IgA) nephropathy, the glomeruli manifested as necrotizing lesions and crescent formation (PAS), 134 and IgA was deposited in the mesangial area of the glomerulus. 135 syndrome, and concomitant hemolytic uremic syndrome, vasculitis, and acute necrotizing glomerulonephritis.…”
Section: Tubular Epithelial Cellsmentioning
confidence: 99%
“…It is generally believed that collapsing glomerulopathy is related to ALOP1 gene mutations, and 36% of patients can achieve partially alleviation of the proteinuria 76,132,140 (Figure 3E). Some patients may also develop granulomatous interstitial nephritis 133 (Figure 3F), IgA nephropathy, and glomerulonephritiscrescentic immunoglobulin A nephropathy 134,135 (Figure 3G). There are also rare reports of membranous nephropathy and T A B L E 2 Mechanism and pathological changes of renal parenchymal cell injury caused by SARS-CoV-2…”
Section: Kidney Pathological Diagnosismentioning
confidence: 99%
See 1 more Smart Citation